Fire Insurance Rates and State Regulation - Gephart, W. F. (Quarterly Journal of Economics, 1914)
I. Introductory; peculiarities as regards fire insurance rates in the United States, 447. — How the price of indemnity differs from ordinary prices, 448. — II. The theory of these rates, 450. — Classification no sure way of measuring hazard, 452. — Analysis of hazard into component parts, 453. — Influence of geographical area, 455. — III. Conflagrations a disturbing factor in the United States, 457. — IV. State regulation of three kinds: (1) Valued policy laws, 458. — (2) Anti-coinsurance laws, 460. — (3) Anti-trust laws, 462. — Conclusion, 464.